Using Inquiry Based Learning Strategy in Teaching Writing Descriptive Text - Mike Amelia; Nostalgianti Citra Prystiananta (Linguistic, English Education and Art (LEEA) Journal, 2021)
This research aimed to look at the effect of inquiry based learning strategy on students’ ability to write a descriptive text. The method of this research was quasi-experiment. The population of this research was eighth-grade students of MTsN Kota Solok. The total population was 65 students. The research results show that the pre-test means score in experimental and control classes was 46,8 and 44,4. The mean score of post-test in the experimental class was 55 and control class 51,6. Students’ ability in writing descriptive text analyzed by using t-test statistical which t calculated= 2,04 and t table (0,975: 38) = 2,02 with significant level t calculated > t table. In conclusion, the students who were taught using an Inquiry based learning strategy have better results in writing descriptive text than those who were taught without inquiry based learning. Keywords: Descriptive text, Inquiry Based Learning, Writing